Analisis Investasi dan Penetapan Harga Jual Rumah Berbasis Hibrid Markup - Internal Rate of Return - Jojok Widodo (Jurnal Poli-Teknologi, 2022)
The increase in population from year to year can affect consumers' number of housing requests. It is an opportunity for investors to conduct investment business in housing projects. But on the other hand, many investors suffer losses from this business due to errors in determining the value of the product price. Therefore, it is necessary to determine the product price and analyze its investment feasibility. The method used in this research is the hybrid mark-up and the Internal Rate of Return (IRR). The mark-up is used to determine the housing products price through Cost Plus Pricing analysis, while investment analysis of the pricing uses IRR. This analysis is implemented in the case study used in Cempaka Village Housing research to produce a real analysis. The results show that the mark-up method using cost-plus pricing can be applied to determine the product price in the housing estate to get a decent profit. The mark-up value that produces a decent profit is 40%, and the selling price according to the types 24/60, 47/72, and 50/72 is Rp 143.550.159, Rp 234.406.509 dan Rp 277.720.507, respectively. The impact of the price-fixing generates several cash flows that can be analyzed using the IRR to determine the feasibility of the investment. The investment analysis results are NPV Rp 1,688,203,568, IRR 13.82%, and PP of almost 12 months. The output of this study also produces a linear regression equation that can be used to predict the IRR value based on the set mark-up value. The resulting linear regression equation is Y = 0,3327 X + 0,0249 with the value of the mark-up effect on the IRR of 92%.